2010
DOI: 10.1002/jsfa.4240
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sulfur‐containing compounds to the colour‐inhibiting effect and improved antioxidant activity of Maillard reaction products of soybean protein hydrolysates

Abstract: Effective colour control of the Maillard reaction by L-cysteine may allow the production of healthier (higher antioxidant activity) and tastier foods to satisfy consumers' and food producers' demands. Light-coloured products might be used as functional flavour enhancers in various food systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…MRPs can also provide distinctive flavor attributes. Strong umami, mouthfulness, continuity, meaty attributes have been demonstrated in cysteine-xylose-soybean peptide model system, as mentioned in our previous study (Huang et al 2011). Ogasawara et al (2006a, b) showed that the Maillard peptides with a molecular weight of 1,000-5,000 Da generated during the ageing of soybean paste affected not only the basic taste qualities but also enhanced mouthfulness and continuity.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…MRPs can also provide distinctive flavor attributes. Strong umami, mouthfulness, continuity, meaty attributes have been demonstrated in cysteine-xylose-soybean peptide model system, as mentioned in our previous study (Huang et al 2011). Ogasawara et al (2006a, b) showed that the Maillard peptides with a molecular weight of 1,000-5,000 Da generated during the ageing of soybean paste affected not only the basic taste qualities but also enhanced mouthfulness and continuity.…”
Section: Introductionsupporting
confidence: 74%
“…Soybean protein isolate (867 g protein.kg Preparation of Maillard reaction products by gradient temperature-elevating method (MRP-60) and isothermal method (PXC and PX) Soybean peptide (1 g) prepared according to the method of Huang et al (2011) and xylose (0.15 g) was suspended in 10 ml de-ionized water. pH was adjusted to 6.5.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations